2021
DOI: 10.1021/acsomega.0c06327
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Silicone Hydrogel Contact Lenses with a Bioinspired 2-Methacryloyloxyethyl Phosphorylcholine Polymer Surface

Abstract: Inspired by the cell membrane surface as well as the ocular tissue, a novel and clinically applicable antifouling silicone hydrogel contact lens material was developed. The unique chemical and biological features on the surface on a silicone hydrogel base substrate were achieved by a cross-linked polymer layer composed of 2-methacryloyloxyethyl phosphorylcholine (MPC), which was considered important for optimal on-eye performance. The effects of the polymer layer on adsorption of biomolecules, such as lipid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 66 publications
0
45
0
Order By: Relevance
“…11 In addition, the PMPC-modified silicone hydrogel contact lens can prevent adsorption of biological components such as lipids and proteins from tears. 12 However, the morphology of the PMPC chains at the interface was not clear. In this study, we observed the morphology of the PMPC layer on the silicone hydrogel contact lens surface and clarified its similarity to the natural corneal tissue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In addition, the PMPC-modified silicone hydrogel contact lens can prevent adsorption of biological components such as lipids and proteins from tears. 12 However, the morphology of the PMPC chains at the interface was not clear. In this study, we observed the morphology of the PMPC layer on the silicone hydrogel contact lens surface and clarified its similarity to the natural corneal tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the surface exhibited superhydrophilicity . In addition, the PMPC-modified silicone hydrogel contact lens can prevent adsorption of biological components such as lipids and proteins from tears . However, the morphology of the PMPC chains at the interface was not clear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface coating or nano-composited mixing [356,357] strategies have been widely employed as current contact lenses lack antibiotic properties. However, long-term stability and biocompatibility require further investigation.…”
Section: Novel Smart Contact Lens Materials With Extraordinary Proper...mentioning
confidence: 99%
“…Considering that the moisture content of pure silicone material is zero, the prepared contact lenses are easy to attach to the cornea due to their hydrophobicity, making the user uncomfortable. Therefore, we developed silicone hydrogel (SL) contact lenses that combine the excellent oxygen permeability of silica gel and the excellent hydrophilicity of conventional hydrogel materials [17][18][19].…”
Section: Introductionmentioning
confidence: 99%